Var Compensation by Evolutionary Programming Considering Harmonics - Pau, K.N.; Venkatesh, B.; Sankaran, P. (2004)
Modern distribution systems employ several power electronic devices. These inject substantial harmonic content into the power lines. This letter proposes a simple technique for computing the optimal values of capacitor and/or inductor banks to be switched in to minimize the line losses. The method uses an evolutionary programming technique. A simple numerical example is also presented.